Level of Knowledge Management among Faculty Members in the Context of Nepali Higher Educational Institution - Paudel, Krishna Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2020)
Knowledge management is taken as an integral component of any institution to enhance organizational effectiveness and productivity. Knowledge Management (KM) in academia is being prioritized these days to enhance academic activities and discourses. The knowledge management impacts to enhance the academic activities in academia, particularly for higher educational institutions (HEIs). Furthermore, the practices of KM enhance academic activities in higher educational institutions. Thus, the purpose of this research was to measure the level of KM among faculty members of HEIs. The quantitative method was used to conduct this research. The tools to measure knowledge management practices among faculty members of HEIs were developed by using Delphi methods. The 445 respondents were taken from the four universities of Nepal. Similarly, the data was taken from these universities as well. The factor analysis was used to identify the dimension of KM. The factor analysis identified seven dimensions of KM; knowledge utilization, acquisition, generation, dissemination, transfer, creation, and presentation. To analyze the level of the knowledge management, mean and standard deviation were used as the indicators or analysis tools for this research. The level of knowledge management was categorized into three groups viz. low, medium, and high. The study found that the overall pace of KM was high except for the knowledge generation process in the context of higher education. Due to individual differences and the organizational environment, culture, and technological infrastructure, it makes the level of knowledge generation differences comparing from other dimensions of knowledge management.